Nathan Philip og engrosfirmaet J. Goldstein & Søn. Overlevelsesstrategi i en jødisk virksomhed under den tyske besættelse - Skov, Lise (Historisk Tidsskrift, 2025)
J. Goldstein & Søn was Denmark’s oldest fur wholesaler, and also its largest before and during the Second World War. Until the Nazi takeover in 1933, Leipzig had been the global capital for the fur trade, and Nathan Philip (1883–1951), the owner-manager of J. Goldstein & Søn, spent several weeks there each year. After the first Nazi boycott of Jewish businesses in Germany in April 1933, Nathan Philip redirected sales to London, engaging a former employee as his agent. He also established a branch in Malmoe, Sweden, which became especially important to him after the German occupation of Denmark on April 9th, 1940. In September 1943, as the German authorities prepared to deport Danish Jews, a warning was passed through Jewish networks. While most were incredulous and unprepared, Nathan Philip enacted the plan he had prepared in advance. On September 20th, he signed a power of attorney, making accountant Eske Hansen his legal guardian with full authority over all his assets. On September 30th, Eske Hansen sold J. Goldstein & Søn to O. Storm-Nielsen, his right-hand man, and the company’s name was changed to O. Storm-Nielsen. The agreed price was just over 1 million DKK, to be paid in ten 100,000 DKK transfers on stipulated dates (it seems that only three such installments were actually paid). On the night of October 1st, Nathan Philip and his family escaped to Sweden. On Philip’s return to Copenhagen in May 1945, Storm-Nielsen wished to continue the company in partnership with Nathan Philip. This led to embittered negotiations between the two men with accountant Eske Hansen as assistant and notetaker. In the end, Nathan Philip bought out Storm-Nielsen for half a million DKK and reestablished J. Goldstein & Søn with himself as the sole owner. The sales contract from 1943 had been robust enough to withstand potential forced aryanization, and remained legally binding to the extent that it could not be dismissed as mere pro forma after the war.